PENGARUH KEPEMIMPINAN, PENGAWASAN DAN SIKAP KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN LABUHANBATU SELATAN - Nurlaili Rambe; Eka Rafika; Muhammad Rahmadani Lubis; Paisal Pahmi Hasibuan; Muhammad Amsal Nasution (Manajemen dan Bisnis, 2021)
The formulation of problem in this research is there is influence  leadership on employees performance. There is influence  controlling on employees performance. There is  work attitude on employees performance. There is influence of  leadership, controlling and  work attitude on employees performance. The purpose of this research is for know influence and analize of   leadership on employees performance. For know influence and analize  controlling on employees performance. For know influence and analize  work attitude on employees performance. For know influence and analize  leadership,  controlling and  work attitude on employees performance.   The sample in this research is 36 employees, with data analysis technique used is multiple linear regression analysis. The research result leadership influence positive and significant on employees performance.  controlling  influence positive and significant to employees performance.  Work attitude influence positive and significant to employees performance.  Leadership,  controlling and  work attitude influence positive and significant to employees performance.